Impact of an Ultra-Endurance Marathon on Cardiac Function in Association with Cardiovascular Biomarkers - Achim Leo Burger; Claudia Wegberger; Maximilian Tscharre; Christoph C. Kaufmann; Marie Muthspiel; Edita Pogran; Matthias K. Freynhofer; Alexander Szalay; Kurt Huber; Bernhard Jäger (SpringerOpen, 2024)
Abstract Background Participation in ultra-endurance races may lead to a transient decline in cardiac function and increased cardiovascular biomarkers. This study aims to assess alterations in biventricular function immediately and five days after the competition in relation to elevation of high-sensitivity cardiac Troponin I (hs-cTnI) and N-terminal-pro-brain-natriuretic-peptide (NT-proBNP). Methods and Results Fifteen participants of an ultramarathon (UM) with a running distance of 130 km were included. Transthoracic echocardiography and quantification of biomarkers was performed before, immediately after and five days after the race. A significant reduction in right ventricular fractional area change (FAC) was observed after the race (48.0 ± 4.6% vs. 46.7 ± 3.8%, p = 0.011) that persisted five days later (48.0 ± 4.6% vs. 46.3 ± 3.9%, p = 0.027). No difference in left ventricular ejection fraction (LVEF) was found (p = 0.510). Upon stratification according to biomarkers, participants with NT-proBNP above the median had a significantly reduced LVEF directly (60.8 ± 3.6% vs. 56.9 ± 4.8%, p = 0.030) and five days after the race (60.8 ± 3.6% vs. 55.3 ± 4.5%, p = 0.007) compared to baseline values. FAC was significantly reduced five days after the race (48.4 ± 5.1 vs. 44.3 ± 3.9, p = 0.044). Athletes with hs-cTnI above the median had a significantly reduced FAC directly after the race (48.1 ± 4.6 vs. 46.5 ± 4.4, p = 0.038), while no difference in LVEF was observed. No alteration in cardiac function was observed if hs-cTnI or NT-proBNP was below the median. Conclusion A slight decline in cardiac function after prolonged strenuous exercise was observed in athletes with an elevation of hs-cTnI and NT-proBNP above the median but not below.